Translation between epochs and cultures: the first Polish version of Geoffrey Chaucer’s A Treatise on the Astrolabe - Wojtyś, Anna (Papers in Linguistics, 2025)
A Treatise on the Astrolabe earned Chaucer the title of “the first technical writer in English” (Basquin 1981: 22). Although it concerns astronomy and astrology, the treatise is written in a simple way (Reidy 2008: 661) as Chaucer wanted it to be read by ten-year-old boys. The selection of such an addressee had impact both on the language of the text and on its form: the treatise contains repetitions, similes facilitating comprehension, explanations, and emphases of important passages. At the same time, it is rooted in the 14th century reality. The key challenge in the preparation of the first Polish translation was determining the function of the text and its recipients. Three major differences between the original and the translation can be distinguished: (1) the age of the reader, as one cannot expect the treatise to be read by children, (2) their background knowledge, as present-day addressees will be professionals interested in the history of astronomy, and (3) the aim of the text, which is a historical source. An additional difficulty was the language of the treatise – mediaeval English with words and collocations closely connected with 14th century English culture. The article aims to show an impact of the above-mentioned factors on the shape of the Polish version by Anna Wojtyś, which will be published shortly.